Assessing the Impact of HRM Practices on Employee Absenteeism with Reference to Remote Employees - Verma, Manish Kumar; Sinha, Ashish Ranjan (International Review of Management and Marketing, 2025)
The study aims to explore the effect of three key HRM practices—Consistency, Distinctiveness, and Consensus—on reducing absenteeism in the workplace. It seeks to understand how these practices influence employees’ attendance and whether they can significantly lower absenteeism rates. The responses were collected from 604 participants using a structured questionnaire. The sample primarily consisted of individuals aged 25-44 from the IT, Marketing, and Finance departments, with most respondents occupying mid-level positions. Data were analyzed using SPSS for descriptive statistics and structural equation modelling with partial least squares (PLS-SEM) to examine the relationships between the factors and test the hypotheses. The study indicates a substantial impact of HRM practices on reducing absenteeism rates. structural equation modeling (SEM) confirms significant positive relationships between Consistency, Distinctiveness and Consensus with reduced absenteeism. Reliability and validity assessments demonstrate high reliability and strong validity for all constructs. The findings suggest that consistent, distinctive, and consensual HRM practices significantly reduce absenteeism among employees.